Carbonaceous Particles from Candle Soot Enhance Water Absorption and Modulate Starch-Sugar Metabolism in Solanaceae Seed Germination - Anca Awal Sembada; Ahmad Faizal; Rizkita Rachmi Esyanti; Yuli Setyo Indartono; I. Wuled Lenggoro (Caraka Tani: Journal of Sustainable Agriculture, 2025)
Candle soot is a source of carbonaceous compounds that has been viewed as unwanted air pollution. Few have attempted to apply candle soot in agriculture, specifically for seed germination. This study was conducted to determine the effect of using candle soot on the germination of seeds from the Solanaceae family (Capsicum annuum, Solanum lycopersicum, and Solanum melongena). Three concentrations (10-2, 10-3, and 10-4 wt%) of candle soot were used. The results showed an improvement in measurable germination parameters and seedling quality parameters. The 10-3 wt% concentration was able to reduce the time needed for germination compared to the control by 11% in C. annuum, 12% in S. lycopersicum, and 10% in S. melongena. Further evaluation was conducted by analyzing the elements present in the seedlings. The results showed that the elemental information of seedlings treated with candle soot did not differ significantly from the control. This indicates that candle soot is biocompatible for agricultural applications. Further evaluation was also carried out to analyze biochemical components such as starch and soluble sugar, which play a crucial role in the seed germination process. The results showed a significant (p < 0.05) decrease in starch content compared to the control, while the soluble sugar content increased during treatment with candle soot. These carbonaceous particles could be a potential approach to enhancing germination and promoting sustainable agricultural practices, as revealed by this investigation.